Masyarakat Kolonis Jawa di Pringsewu Tahun 1925-1945 - Astri Kurnia Dewi; Ali Imron; Hendry Susanto (FKIP UNIVERSITAS LAMPUNG, 2017)
The problem of the research was formulated as: what factors has caused the migration of Java colonists to Pringsewu region? How is the socio-economic condition of the Java colonists in Pringsewu in the year of 1925-1945? The purpose of this research was to find out the factors that trigger the migration of Java colonists to Pringsewu and also the socio-economic conditions of Java colonists in Pringsewu in the year of 1925-1945. The method used in this study was historical method. The results of the research showed that the migration of Java colonists has been triggered by two factors, namely the driving and the withdrawal factors; while the socio economic conditions of Java colonists in Pringsewu in the year of 1925-1945 revealed a good relationship between the indigenous people and the immigrants; also in health, education, and agriculture improvement such as land expansion for agriculture and in increasing rice production.Rumusan masalah dalam penelitian ini adalah apa sajakah faktor perpindahan kolonis Jawa ke Pringsewu dan kondisi sosial ekonomi kolonis Jawa di Pringsewu Tahun 1925-1945? Tujuan dalam penelitian ini adalah untuk mengetahui faktor apasaja yang memicu perpindahan kolonis Jawa ke Pringsewu dan bagaimana kondisi sosial ekonomi kolonis Jawa di Pringsewu Tahun 1925-1945. Metode yang digunakan dalam penelitian ini adalah metode historis. Hasil penelitian yang di peroleh adalah faktor perpindahan kolonis terdiri dari faktor pendorong dan penarik serta kondisi sosial ekonomi kolonis Jawa di Pringsewu Tahun 1925-1945 adalah terjadinya hubungan yang baik antar penduduk asli dan pendatang, bidang kesehatan, pendidikan, peningkatan dalam bidang pertanian seperti perluasan lahan pertanian dan peningkatan produksi beras.Kata kunci: jawa, kolonis, pringsewu